E-Commerce dan Transaction Security: Menjaga Customer Trust Pada Pelaku Konsumen Spaylater Generasi Z di Sidoarjo - Hurum, Hurum Azzahra Amaliya; Edita Rachma Kamila; Nurul Kholifah; Nur Afiqfah; Muhammad Burhan Rokbani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of information technology has driven the growth of e-commerce significantly, including in Indonesia. Shopee, as one of the main platforms, continues to innovate through features such as Shopee PayLater which provides payment flexibility, especially for Generation Z. However, increasing use of this service also raises challenges related to transaction security, which is an important factor in building customer trust. This research aims to analyze the influence of e-commerce and transaction security on customer trust of Generation Z Spaylater consumers in Sidoarjo. Using descriptive quantitative methods and purposive sampling techniques, data was collected from 70 respondents and analyzed using SmartPLS 4.0. The research results show that 1) e-commerce has a positive and significant influence on customer trust 2) transaction security has a positive and significant influence on customer trust.